Non-Pharmacologic Interventions in COVID-19 Pandemic Management; a Systematic Review - Etemad, Koorosh; Mohseni, Parisa; Shojaei, Saeideh; Mousavi, Seyed Ali; Taherkhani, Shakiba; Fallah Atatalab, Fatemeh; Ghajari, Hadis; Hashemi Nazari, Seyed Saeed; Karami, Manoochehr; Karami, Manoochehr; Izadi, Neda; Hajipour , Mahmoud (Archives of Academic Emergency Medicine, 2023)
Introduction: Different countries throughout the world have adopted non-pharmacologic interventions to reduce and control SARS - CoV-2. In this systematic approach, the impact of non-pharmacologic interventions in management of COVID-19 pandemic was assessed. Methods: Following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, systematic search was carried out on the basis of a search strategy on PubMed, Web of Science, Scopus, and WHO databases on COVID-19. The impact of travel ban, personal protective equipment, distancing, contact tracing, school closure, and social distancing and the combined effect of interventions on COVID-19 were assessed. Results: Of the 14,857 articles found, 44 were relevant. Studies in different countries have shown that various non-pharmacological interventions have been used during the COVID-19 pandemic. The travel ban, either locally or internationally in most of the countries, movement restriction, social distancing, lockdown, Personal Protective Equipment (PPE), quarantine, school closure, work place closure, and contact tracing had a significant impact on the reduction of mortality or morbidity of COVID-19. Conclusion: Evidence shows that the implementation of non-pharmacologic interventions (NPIs), for example, social distancing, quarantine, and personal protective equipment’s are generally effective and the best way to prevent or reduce transmission. However, this study suggests that the effectiveness of any NPI alone is probably limited, thus, a combination of various actions, for example, social distancing, isolation, and quarantine, distancing in the workplace and use of personal protective equipment, is more effective in reducing COVID-19.